Dominansi dan Keragaman Gulma Pada Tanaman Jagung (Zea mays L.) dengan Sistem Tanam Konvensional dan Jajar Legowo - Rahmadi, Rizky; Rochman, Fajar; Dulbari, Dulbari; Priyadi, Priyadi; Sari, Resti Puspa Kartika; Widyani, Dimas Prakoso; Ashadi, Ibnu (Universitas Musamus, Merauke, Papua, 2024)
The presence of weeds is a significant factor that contributes to the decline in maize yield. To reduce yield loss, appropriate weed control methods must be applied. The first step in determining these methods is to identify weed dominance and diversity. This study aims to identify the dominance and diversity of weeds in three corn planting systems: conventional, jajar legowo 1:2, and 1:3 spacing. The research was conducted at the Teaching Farm Polinela Organic Farm in Lampung Province from November to December 2023. Vegetation analysis was performed using a 0.5 m2 quadrant randomly placed on 10 plots of land. The dominance value of weeds was determined using the Summed Dominance Ratio (SDR) value, while the diversity of weeds was measured using the Shanon-Wiener index value (H'). The study found that the conventional field had 9 weed species, the 1:2 legowo field had 8 weed species, and the 1:3 legowo field had 5 weed species. Ageratum conyzoides was the dominant broadleaf weed species in both the conventional corn field and jajar legowo 1:2, while Asystasia gangetica dominated the jajar legowo 1:3 corn field. The weed diversity index analysis results for the three corn planting systems fall into the medium category. Specifically, the results are 2.12 for conventional corn fields, 1.94 for 1:2 jajar legowo corn fields, and 1.3 for 1:3 jajar legowo corn fields.